Role of p53 Gene in Breast Cancer: Focus on Mutation Spectrum and Therapeutic Strategies - Kaur, Raman P.; Vasudeva, Kanika; Kumar, Roshan; Munshi, Anjana (Current Pharmaceutical Design, 2018)
TP53 is a tumor suppressor gene which is commonly mutated in various cancers including breast cancer. Alterations in the gene lead to an altered expression of various genes that are directly or indirectly under the transcriptional control of p53. This results in malfunctioning of DNA damage repair pathways, cell-cycle arrest, chromatin remodeling and apoptosis. Different mutations in TP53 gene have been reported in different ethnic groups and exon 4 and intron 3 are reported to be frequently mutated in breast cancer patients especially triplenegative breast cancer. Increased global burden of TP53 mutated breast tumors has paved the path for various therapies targeting p53/TP53. Numerous molecules including nutilins, MI series, RO5693, PRIMA-1, RITA, etc. have been developed. Majority of these restore p53/TP53 function by targeting negative regulators of p53/TP53, wtp53/TP53 (wild-type) and mtp53/TP53 (mutant). Most of these molecules are in the preclinical phase except for two APR-246 and COTI-2 that have progressed to clinical trials. The current review has been compiled with an aim to give an overview of mutations in p53 across various ethnic groups, the effect of these alterations on TP53 function and the therapeutic strategies developed till date targeting p53/TP53 especially in breast cancer.
Keywords: asians